Волинцевська культура на Правобережному Подніпров’ї (за матеріалами Ходосівського поселення) - Петрашенко, В.О. (Археологія, 1989)
Стаття порушує питання про хронологію, етнічну належність групи пам’яток VIII— IX ст. на Правобережному Подніпров’ї, що увійшли в літературу як волинцевські.
На основі аналізу речових знахідок і кераміки з найбільш дослідженого поселення
поблизу с. Ходосівка зроблено висновок про тотожність сахнівських і волинцевських старожитностей і їх безпосереднє переростання у Київську Русь на Правобережному Подніпров’ї. В статье публикуются новые материалы у с. Ходосовка, добытые автором во время раскопок в 1985 г. Анализ всех категорий археологических находок, а также топография, тип жилищ и застройка, весь культурно-хозяйственный комплекс сближает исследуемый памятник как с волынцевской культурой, так и памятниками типа Сахновки, что позволило высказать точку зрения о единстве этих археологических проявлений. Автор полемизирует в вопросе о генетической связи памятников типа Сахновки и Пеньковскими, развивая точку зрения об автохтонности сахновско-волынцевских древностей на Правобережье, обращается также внимание на факт их перерастания в культуру ранней Киевской Руси. The paper presents information about new findings obtained by the author during excavations near vil. Khodosovka in 1985. Analysis of all the categories of archaeological findings as well as topography, type of dwellings and buildings, the whole cultural-economic complex bring the monument under study closer both to the Volyntsevian culture and to the Sakhnovka-type monuments, that permitted advancing an opinion on the unity of these archaeological manifestations. The author argues in the problem on genetic relation of the Sakhnovka-type and Penkovka-type monuments, developing a standpoint on the autochthonous character of the Sakhnovka-Volyntsevian antiquities in the right-bank territory. A fact of their development into the culture of the early Kiev Rus is given attention as well.